Ben Lee performing at Vodafone Live at the Chapel, Melbourne, 5 December 2005 - Philbey, Martin, 1962- (2005)
Vodafone Live At The Chapel, a music event featuring performances by local and international musicians.
Title devised by cataloguer based on information supplied by photographer.
Part of the collection: Australian music industry and performers, 1998-2008.
Acquired in digital format; access copy available online.
Mode of access: Internet via World Wide Web.
Purchased from the photographer, 2009.
Keywords: Lee, Ben, -- 1978- -- Portraits; Musicians -- Victoria -- Melbourne -- Portraits; Singers -- Victoria -- Melbourne -- Portraits; Guitarists -- Victoria -- Melbourne -- Portraits; Entertainment events -- Victoria -- Melbourne -- Photographs; Musicians; Singers